Dynamics of androgens in healthy and hospitalized newborn foals - Jacob M. Swink; Lindsey M. Rings; Hailey A. Snyder; Rachel C. McAuley; Teresa A. Burns; Katarzyna A. Dembek; William F. Gilsenan; Nimet Browne; Ramiro E. Toribio (Journal of Veterinary Internal Medicine, 2021)
Abstract Background Information on steroids derived from the adrenal glands, gonads, or fetoplacental unit is minimal in newborn foals. Objective To measure androgen concentrations in serum and determine their association with disease severity and outcome in hospitalized foals. Animals Hospitalized (n = 145) and healthy (n = 80) foals. Methods Prospective, multicenter, cross‐sectional study. Foals of ≤3 days of age from 3 hospitals and horse farms were classified as healthy and hospitalized (septic, sick nonseptic, neonatal maladjustment syndrome [NMS]) based on physical exam, medical history, and laboratory findings. Serum androgen and plasma ACTH concentrations were measured with immunoassays. Data were analyzed by nonparametric methods and univariate analysis. Results Serum dehydroepiandrosterone (DHEA), androstenedione, testosterone, and dihydrotestosterone (DHT) concentrations were higher upon admission in hospitalized foals (P <  .05), were associated with nonsurvival, decreased to 4.9‐10.8%, 5.7‐31%, and 30.8‐62.8% admission values in healthy, SNS, and septic foals, respectively (P < .05), but remained unchanged or increased in nonsurviving foals. ACTH:androgen ratios were higher in septic and NMS foals (P < .05). Foals with decreased androgen clearance were more likely to die (odds ratio > 3; P < .05). Conclusions and Clinical Importance Similar to glucocorticoids, mineralocorticoids, and progestagens, increased serum concentrations of androgens are associated with disease severity and adverse outcome in hospitalized newborn foals. In healthy foals, androgens decrease over time, however, remain elevated longer in septic and nonsurviving foals. Androgens could play a role in or reflect a response to disorders such as sepsis or NMS in newborn foals.